2015
DOI: 10.1002/jbt.21725
|View full text |Cite
|
Sign up to set email alerts
|

Isoform-Specific Regulation of Mouse Carboxylesterase Expression and Activity by Prototypical Transcriptional Activators

Abstract: Nuclear receptors and transcription factors regulate the mRNA expression of many drug metabolizing enzymes, including the carboxylesterases (Ces). However, there are few data regarding whether these changes in mRNA expression result in alteration of protein levels or activity. In the present study, we sought to determine the isoform-specific regulation of hepatic Ces mRNA expression and activity following administration of pharmacological activators of the constitutive androstane receptor (CAR), pregnane X rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…As the promoting roles for lipolysis by CES2 has been well illustrated ( Li et al, 2016 ; Chalhoub et al, 2021 ), we thus speculate that bicyclol could also enhance the lipolysis process. Of note, PPARα and CES2 were downstream targets of p62-Nrf2 signaling ( Zhang et al, 2012 ; Baker et al, 2015 ; Tao et al, 2021 ). Our results further verified the protein expressions of p62 and Nrf2 were reduced significantly in WD- and WD/CCl 4 -induced model groups, while bicyclol but not berberine increased their expressions ( Figures 3A, B ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the promoting roles for lipolysis by CES2 has been well illustrated ( Li et al, 2016 ; Chalhoub et al, 2021 ), we thus speculate that bicyclol could also enhance the lipolysis process. Of note, PPARα and CES2 were downstream targets of p62-Nrf2 signaling ( Zhang et al, 2012 ; Baker et al, 2015 ; Tao et al, 2021 ). Our results further verified the protein expressions of p62 and Nrf2 were reduced significantly in WD- and WD/CCl 4 -induced model groups, while bicyclol but not berberine increased their expressions ( Figures 3A, B ).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, bicyclol also enhanced the PPARα-mediated β-oxidation, and this role was also verified by previous report ( Yu et al, 2009 ). Generally, CES2 was independent of the expression of PPARα ( Wen et al, 2019 ), while all of them could be regulated by the pleiotropic transcription factor Nrf2 ( Zhang et al, 2012 ; Baker et al, 2015 ; Tao et al, 2021 ). Nrf2 induced the downstream PPARα expression and was regulated by its upstream increased p62 to connect with Keap1 ( Zhang et al, 2012 ; Baker et al, 2015 ; Lee et al, 2020 ; Tao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that PFOA activates nuclear receptors including PPARα and CAR (Poole et al, 2001;Rosen et al, 2008) that may alter hepatic Ces expression/activity (Baker et al, 2015). As shown in Fig.…”
Section: Transcription Factor and Target Gene Expression In Livers Frmentioning
confidence: 82%
“…Ces enzyme activity in mouse hepatic microsomal fractions was determined by the hydrolysis of p-nitrophenyl valerate using a continuous spectrophotometric assay as described previously (Baker et al, 2015). Briefly, frozen livers (0.1-0.2 g) were homogenized in buffer (0.05 M Tris-HCl, 1.15% KCl, pH 7.4) and centrifugated at 9000 × g for 20 min at 4°C.…”
Section: Ces Enzyme Activity Assaymentioning
confidence: 99%
See 1 more Smart Citation